천연 소재 복합물이 고지방사료로 유도된 비만 생쥐의 조직형태 및 조직병리학적 변화에 미치는 영향 - 신인순; In Soon Shin; 최혜민; Hye Min Choi; 구세광; Sae Kwang Ku; 김미려; Mi Ryeo Kim (大韓本草學會誌, 2012)
Objective : Obesity is often defined as a condition associated with accumulations of excessive body fats which resulting from disorder of energy balance in term of energy intake and energy expenditure. Methods : The effects of natural mixture (T) for inhibition of lipid metabolism on the liver, epididymal fat pads and pancreatic zymogen granules of high fat diet (HFD) supplied rats were observed by histopathology and histomorphometry. Results : As results of HFD supply, severe steatohepatitis such as increases of mean diameters of hepatocytes and the percentages regions of fatty changes was detected. In addition, hypertrophy of adipocytes (increase of mean diameters of epididymal fat pads) was also detected with dramatic decreases of pancreatic zymogen granules at histopathological and histomorphometrical observations. However, theses steatohepatitis and hypertrophy of adipocytes induced by HFD supply were inhibited by treatment of 5 % and 10 % T (T5, T10), respectively. Well corresponded as the results of adipocyte hypertrophy and steatohepatitis, the decreases of pancreatic zymogen granules were also dose-dependently inhibited by T treatment as compared with HFD control, respectively. Conclusion : In conclusion, based on the results, it is considered that test materials, T5 and T10, will be showed hepatoprotective and anti-obese effects, may be directly and/or indirectly mediated by pancreatic zymogen granules because they dose-dependently inhibited steatohepatitis, hypertrophy of adipocytes and decreases of pancreatic zymogen granules induced by HFD supply, respectively.